Central alpha(2) adrenergic receptors and cholinergic-induced salivation in rats - Takakura, ACT; Moreira, T. D.; De Luca, L. A.; Renzi, Antonio [UNESP]; Menani, José Vanderlei [UNESP] (Elsevier B.V., 2003)
Salivation induced by intraperitoneal (i.p.) injections of pilocarpine (cholinergic agonist) is reduced by intracerebroventricular (i.c.v.) injections of moxonidine (alpha(2) adrenergic and imidazoline receptor agonist). In the present study, we investigated the involvement of central alpha(2) adrenergic receptors in the inhibitory effect of i.c.v. moxonidine on i.p. pilocarpine-induced salivation. Male Holtzman rats with stainless steel cannula implanted into the lateral ventricle (LV) were used. Saliva was collected using pre-weighted small cotton balls inserted into the animal's mouth under ketamine (100 mg kg(-1)) anesthesia. Salivation was induced by i.p. injection of pilocarpine (4 mu mol kg(-1)). Pilocarpine-induced salivation was reduced by i.c.v. injection of moxonidine (10 nmol) and enhanced by i.c.v. injections of either RX 821002 (160 nmol) or yohimbine (320 nmol). The inhibitory effect of i.c.v. moxonidine on pilocarpine-induced salivation was abolished by prior i.c.v. injections of the alpha(2) adrenergic receptor antagonists, RX 821002 (160 nmol) or yohimbine (160 and 320 nmol). The alpha(1) adrenergic receptor antagonist prazosin (320 nmol) injected i.c.v. did not change the effect of moxonidine on pilocarpine-induced salivation. The results suggest that moxonidine acts on central alpha(2) adrenergic receptors to inhibit pilocarpine-induced salivation, and that this salivation is tonically inhibited by central alpha(2) adrenergic receptors. (C) 2002 Elsevier B.V. All rights reserved.
Keywords: salivary secretion; parasympathetic; moxonidine; pilocarpine; yohimbine; RX 821002